Fundamental Factors of Financial Ratios and Discretionary Accruals in Influencing the Companies’ Fixed-Asset Investment Decisions - Evangeline Rosa; Hasan Mukhibad (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study aims to empirically prove the influence of profitability, solvency, liquidity, activity, dividend policy, and discretionary accruals on fixed-asset investment decisions.Design/Methodology/Approach: The researchers used consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2013 to 2019. Using the purposive sampling method, this study resulted in 163 bank-year observations. The data were then analyzed utilizing a fixed-effect model.Research findings: The results showed that profitability, liquidity, activity, and discretionary accruals positively affected fixed-asset investment. Meanwhile, the dividend policy negatively affected fixed-asset investment. This study strengthens the pecking order theory. In addition, the research sample used internal funds as a funding source for investment in fixed assets.Theoretical contribution/Originality: The variable added in the study distinguishing it from previous researchers is the discretionary accrual variable. Discretionary accruals have been proven to impact resource allocation, one of which is investment decisions. The additional discretionary accruals variable is expected to strengthen the influence of the consumer goods companies' fundamental factors on investment decisions in fixed assets.Practitioner/Policy implication: Investment in fixed assets in the consumer goods companies uses internal funds because these funds are low risk and support the company's sustainability.Research limitation/Implication: This study used dividend policy as one of the independent variables, and companies that did not distribute dividends could not be sampled.